High or low volume beetroot juice supplementation might positively affect physical capacity and isokinetic muscle function in power athletes - Sakong, H.; Cho, Y.-H.; Seo, T.-B. (Isokinetics and Exercise Science, 2023)
BACKGROUND: Beetroot juice is an ergogenic aid containing high levels of nitrate and is known to have many physiological benefits.